Theoretical and Conceptual Framework for Challenges which Learners with Physical Disabilities Face in Schools in Zambia - Kandimba Humphry; Penda Annie (International Journal of Research in Informative Science Application & Techniques (IJRISAT), 2022)
This manuscript is an extract of a theoretical framework and conceptual framework from a master’s an on-going study on the challenges which learners with physical disabilities face in schools in Zambia. the frameworks suggests that, among the challenges which learners with physical disabilities face in schools in Zambia are the environmental challenges, attitudinal challenges, institutional challenges and financial challenges. It is argued that if challenges are identified and addressed learners with physical disability can benefit a lot from education system and participate in society on equal basis with others.